Offshore Oil and Gas Activities in Arctic areas - Karlström Thylander, Emma (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2013)
The aim of this thesis report is to investigate how existing Best Available Techniques (BAT) for some key systems are affected by Arctic conditions and future expected requirements in Norway. The thesis report is focusing on assessing three systems with the most planned emissions to air and discharges to sea in oil and gas production facilities; Power and Heat generation, Flare system and Produced Water system. The thesis has been conducted in cooperation with Det Norske Veritas in Høvik, Norway during spring of 2013. This report consists of two parts; the first part involves the context and general settings on the Norwegian Continental shelf and the Arctic areas. This includes the oil and natural gas industry in Norway, identified environmental impacts and Arctic conditions. The existing regulation and guidelines on the Norwegian Continental shelf have been summarized and future requirements and guidelines for the Arctic areas have been considered and assessed to as large extent as possible. The second part consists of the findings of existing BAT and expected changes due to Arctic conditions for the key systems studied. By comparing the technical constraints and the environmental requirements the alternatives have been assessed if appropriate for Arctic conditions. The findings include expectations of stricter requirements for the Arctic areas in Norway at present and, depending on case, probably even stricter in the future. This will affect the existing BAT when applied with the expected requirements and the Arctic conditions. In general there are increased requirements when it comes to discharges to sea where the target of zero discharges is emphasized. Norway has both long term target to reduce emissions to air and to be carbon neutral in the future and to protect flora and fauna in the Arctic areas. What in general can be said from the findings are that there will probably be changes and effects on the existing BAT alternatives with Arctic conditions, mainly due to lower temperatures, remoteness and ...